Effect of Position and Age of Cuttings and Auxins on Induction and Growth of Roots in Dalbergia sissoo Roxb. - Ansari, S. A.; Kumar, Pramod; Mandal, A. K. (Indian Forester, 1995)
The response of branch cuttings of D. sissoo was variable with regard to synthetic auxin application, diameter class and age of donor trees.1AA proved much effective for induction and NAA, for growth of adventitious roots. The response pattern for induction of rooting was in the order: Young cutting > thin cutting > thick cutting. The physiological basis for such behaviour has been discussed.